Fulfilling the Rights And Obligations Of The Ldr / Long Distance Relationship Family : Analysis Of The Vow Of Taklik Talak In Marriage Case Study Of Pekalongan District - Liana Mas’udah; Uswatun Khasanah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
There have been countless events that occur in marriage issues that intersect with the rights and obligations of a family to lead to a sakinah family, as happens to families who experience LDR with their spouses often violate as stated in the pledge of ta'lik talaq such as not fulfilling the dhohir and mental income continuously (6 months and even more than a year) to abandon their family without give news and provide for his family. The formulation of the problem in this study: how to fulfill the rights and obligations of LDR families and how to study Islamic law on the fulfillment of the rights and obligations of LDR families based on the pledge of taklik talaq in Pekalongan Regency. The purpose of this study is to find facts about the things that LDR families in Pekalongan Regency strive for the fulfillment of their rights and obligations and identify cases that occur in LDR families in Pekalongan Regency based on the content of the talaq pledge. This research is a type of field research with a sociological normative approach. The types of data used include primary and secondary data. The primary data sources are informants from several LDR family couples in Pekalongan Regency and communities related to this research, while the secondary data includes normative materials and other supporting documents related to the research. All data was collected through interviews and documentation. The Theory of Rights and Duties of Husband and Wife and the content agreement of ta'lik talaq became the basis of the theory used. Based on the data analysis conducted, it was concluded that there are still LDR family couples who violate the content of talaq ta'lik, especially related to the rights of wives and children that have not been fulfilled for several months. Eventually they became victims of LDR and there are still many of these couples who do not understand the meaning of the contents of ta'lik talaq which contains the husband's agreement to his wife and family.